Multicriteria Optimization via Parameter Space Investigation for Ultralow-Altitude Airdrop L1 Adaptive Controller - Zhu, Peng; Dong, Wenhan; Mao, Yuhao; Liu, Ri (International journal of aeronautical and space sciences, 2020)
This paper presents preliminary results of the application of the parameter space investigation method for the design of the L1 flight control system implemented on the ultralow-altitude airdrop process. In particular, the study has established the task performance level of airdrop mission which is chosen as the optimization objective in this paper. According to the characteristics of ultralow-altitude airdrop process, 12 optimization criteria are designated as the constraints during the multicriteria optimization. After two iterations, the task performance level of the airdrop is improved from “Moderate” to “Expected”. The results in the paper confirms the suitability of the parameter space investigation method for the multicriteria design optimization of an airdrop flight control system subject to desired control specifications. In addition, the robustness and dynamic response of the flight control system are significantly improved after optimization. Moreover, the analysis of optimization results has contributed to a deeper understanding of the relationship between L1 controller parameters and airdrop task performance.